Generation of a fibroblast chemotactic factor in serum by activation of complement. - Postlethwaite, A E (1979)
When serum complement is activated by either the classical or alternative pathways, a factor with an apparent 80,000 mol wt is generated that is chemotactic for human dermal fibroblasts. The origin of this serum-derived chemotactic factor (SDCF) is not known; however, it may be a cleavage product from C5 because it is inactivated by monospecific antiserum to human C5, and it is not generated when the complement system is activated in human serum deficient in C5. SDCF is not chemotactic for human neutrophils or monocytes. Because SDCF is generated when serum complement is activated, it may function in vivo to attract connective tissue fibroblasts to sites of inflammatory reactions in which the complement system participates.